The influence of risk or protective factors for suicide ideation - Santos,Walberto Silva dos (2016)
Suicide is understood as a multidimensional act and is caused by the complex interaction of several factors. This study aims to identify the influence of life satisfaction, general health (anxiety and depression) and religious commitment in suicidal ideation. Specifically, this study aims to investigate the predictive power of these factors in suicidal behavior and the relationship between them. To do so, this study counted with 257 participants, aged between 18 and 56 years (M = 22.9, SD = 6.76), mostly single (91.8%), female (62.6%) and Catholic (50.6%). Participants answered: (1) General Health Questionnaire; (2) Satisfaction with Life Scale; (3) Religious Practices Scale; (4) Religious Beliefs Scale; (5) Multi-Attitude Suicide Tendency Scale (MAST); and demographic questions. Results indicated significant correlations between the factors of MAST and the other constructs assessed in this study. Furthermore, satisfaction with life, depression and religious commitment satisfactorily predicted attraction to life and repulsion by life. Thus, these results support satisfaction with life, depression and religious commitment as protective and risk factors of suicidal ideation.